Methamphetamine Increases LPS-Mediated Expression of IL-8, TNF-α and IL-1β in Human Macrophages through Common Signaling Pathways - Liu, Xun (Public Library of Science, 2012)
The use of methamphetamine (MA) has increased in recent years, and is a major health concern throughout the world. The use of MA has been associated with an increased risk of acquiring HIV-1, along with an increased probability of the acquisition of various sexually transmitted infections. In order to determine the potential effects of MA exposure in the context of an infectious agent, U937 macrophages were exposed to various combinations of MA and bacterial lipopolysaccharide (LPS). Treatment with MA alone caused significant increases in the levels of TNF-α, while treatment with both MA and LPS resulted in significant increases in TNF-α, IL-1β and the chemokine IL-8. The increases in cytokine or chemokine levels seen when cells were treated with both LPS and MA were generally greater than those increases observed when cells were treated with only LPS. Treatment with chemical inhibitors demonstrated that the signal transduction pathways including NF-kB, MAPK, and PI3-Akt were involved in mediating the increased inflammatory response. As discussed in the paper, these pathways appear to be utilized by both MA and LPS, in the induction of these inflammatory mediators. Since these pathways are involved in the induction of inflammation in response to other pathogens, this suggests that MA-exacerbated inflammation may be a common feature of infectious disease in MA abusers.